Mathematical Model of Flat Defect's Position on Car Wheel on Account of Suspension Mechanism Resistance and Vertical Roughness of the Rail - D. S. Garipov; L. V. Kudyurov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2010)
In the article the problem of developing a flat defect (“slider”) on the surface of riding the car wheel at various speeds is dealt with. It is shown, that residual vertical deformation considerably decreases at speeds less than critical as early as during the first. Later on deformation decreases slower due to the increase of the area of contact and strengthening of material when multicyclic loading is applied. At speeds higher than critical one the front edge of the “slider” loses contact with the rail, and the wheel hits the rail with the back edge of the newly formed area at every cycle. Rolling of the “slider” takes place. The influence of rigidity of suspension bracket and unevenness of track on the developing of “slider” at low speeds is slight, but it becomes greater at speeds higher than critical one.